Micro-structured optical fiber for sensing applications - Lee, Nicholas Wayne (Nanyang Technological University, 2020)
Optical fibers are expansively applicable to multiple industries such as engineering, medical, and most commonly in telecommunications. In more recent times, optical fibers have also played a significant role for their sensing applications which have proved to perform better than conventional sensors under various circumstances. There has been a growing interest in the development of fiber sensors using photonic crystal fibers (PCF), due to the flexibility and array of their designs which enables constant innovative methods of sensor development. In this project, experiments have been conducted with 7-hole PCF to test the feasibility of its development as a temperature sensor. The method involved selectively infiltrating ethanol of two different concentrations, with refractive indexes of 1.3495 and 1.608, into two of the air claddings in opposition of each other. The layer of ethanol in the air cladding and the outer layer silica cladding forms a double-layered Fabry-Pérot resonator. As a result of the thermo- optic effect of ethanol, the measured temperature sensitivity of the ethanol with lower concentration is -0.1893nm/° , while the temperature sensitivity of the ethanol with higher concentration is -0.2214nm/° . With the results achieved, the 7-hole PCF is viable for use in future developments of a temperature sensor.